Social program of temporary employment works Peru and the quality of life in the inhabitants of the District of Picsi - Samillán Rodríguez, Daniel (2018)
The present study called Social Work Program for temporary employment Trabaja Perú and the quality of life in the inhabitants of the District of Picsi, Province of Chiclayo, Lambayeque Region, 2015, had the objective of evaluating the impact of the Social Inclusive Temporary Employment Program. Peru in relation to the improvement of the quality of life in the beneficiaries of the district of Picsi. The design of the present study was non-experimental transversal, which involved the measurement of the variables, where the description and interpretation of the results obtained was observed. At the same time, the study involved the application of surveys to 134 residents of the Picsi district, where 67 of them were participants in the Trabaja Perú program. It was concluded that there is a very good acceptance with more than 70% of the participants of the program. Finally, it is recommended that the zonal and line management units continuously improve the supervision and monitoring of the Trabaja Peru projects in order to generate temporary jobs and be able to complete the works in due time.